Predicting the effect of droplet geometry and size distribution on atmospheric corrosion. (1st July 2022) - Van den Steen, N.; Gonzalez-Garcia, Y.; Mol, J.M.C.; Terryn, H.; Van Ingelgem, Y.
Abstract: A new approach is proposed to numerically predict and study atmospheric corrosion for ranging droplet size distributions and the influence of the droplet geometry. The proposed methodology allows for a corrosion prediction based on observed droplet size distributions and droplet contact angles. A mechanistic finite element model, including oxygen transport and Butler-Volmer kinetics, is solved in order to obtain the current density as a function of the droplet geometry. This is done for a range of both droplet radii and contact angles. The computed corrosion current densities are then used as input for imposed droplet size distributions. This allows for a calculated material loss estimation for different distributions and electrolyte configurations and shows the extent of the impact of the droplet size distribution on atmospheric corrosion. Highlights: Numerical approach to evaluate corrosion under given droplet size distributions. Applying steady-state, FEM single droplet model with imposed droplet distribution. Evaluating effect contact angle and average droplet radius on corrosion. For the considered distributions, surface area is the critical parameter.